(untitled) - Ralph P Grimaldi (Reading, Massachusetts, 1994)
The book introduces discrete methods that stress the finite nature inherent in many problems and structures; combinatorics - the algebra of enumeration, or counting; graph theory with its applications and interrelations with areas such as data structures and methodss of optimization; and finite algebraic structures that arise in conjunction with disciplines such as coding theory, methods of enumeration, gating networks, and combinatorial designs
Toán rời rạc
Keywords: combinatorial analysis,computer science - mathematics,mathematics